#MeToo dans l’édition : tout le monde savait - Un collectif de plus de 100 personnalités de l'édition (Libération, 2021)
Plus d’une centaine de femmes travaillant dans le livre signent un texte dénonçant un climat délétère et des inégalités flagrantes. Elles demandent que les entreprises de l’édition prennent leur responsabilité.
Keywords: 2000 à aujourd'hui; 2010-2019; 2020-2029; approches et analyses; europe; france; inégalités; metoo; patriarcat; périodes historiques; ressource en ligne; régions géographiques; systèmes d'oppressions; thématiques; travail; violences; violences sexistes et sexuelles

C'est quoi la violence symbolique. #sociologie #bourdieu #sociologie #politique - Cyril CHEVROT (2021)
Résumé du concept de violence symbolique chez Bourdieu et en particulier dans son livre Domination masculine.
Keywords: approches et analyses; cours; discipline; patriarcat; pol5480; premier cycle; ressource en ligne; sciences humaines; sexisme; sociologie; systèmes d'oppressions; thématiques; violences

Ecoféminismes Radical - Bahaffou, Myriam (Feu! : abécédaire des féminismes présents, 2021)
Plutôt que de réduire le féminisme à des revendications faites à l’État, au patron, au chef ou à papa, pour plus de lois, plus de “sécurité”, à n’être que le porte-drapeau ou le cache-misère du capitalisme, de tel ou tel gouvernement nationaliste, ces histoires des féminismes présents rappellent et font résonner ensemble nos vies féministes. Ce livre fonctionne comme un abécédaire, un manuel, une boîte à outils, un dictionnaire amoureux, dans lequel échanger des idées, affûter des armes, écouter des voix, partager des expériences et des pratiques, vibrer pour des luttes présentes. Il s’adresse à tous·tes : il contient à la fois des ressources et foisonne de références utiles, de notions, mais il est fabriqué par des plumes et des voix, des points de vue situés sur des retours d’expériences collectives, des itinéraires politiques et intimes, des réflexions et des rétrospections sur des parcours, des engagements, des révoltes et des espoirs. En pluralisant les styles, en se situant à la fois du côté de la théorie et de la pratique, de la création, des écritures au “nous” et au “je”, il témoigne de la force d’une approche féministe de l’histoire intellectuelle et politique. Il est dédié à toutes les résistantes anonymes au quotidien des violences les plus crasses, à celles qui embrasent les tribunaux, cassent des genoux et brisent les vitrines, à celles qui inventent mille tactiques imperceptibles pour survivre et se mettre à l’abri, à la mémoire de celles dont les noms recouvrent les murs de nos villes la nuit, à la puissance des collectifs qui se font, à ceux qui se sont défaits, qui se sont (re)constitués ailleurs ou autrement, à ce qui nous lie.
Keywords: approches et analyses; cours; discours dominant; fem3100; féminisme décolonial; genre; identités LGBTQIA2+; inégalités; patriarcat; premier cycle; systèmes d'oppressions; thématiques; violences; écoféminisme

The feminist political economy of Covid-19: Capitalism, women, and work. - Cohen, Jennifer; van der Meulen Rodgers, Yana (Global public health, 2021)
Analysing the pandemic through a feminist political economy lens makes clear how gender, race, and class structures are crucial to the functioning of capitalism and to understanding the impacts of the pandemic. The way capital organises production and reproduction combines with structures of oppression, generating vulnerability among the racialised and gendered populations worst impacted by Covid-19. Using global data, this commentary shows that during the pandemic, women experienced relatively greater employment losses, were more likely to work in essential jobs, and experienced a greater reduction in income. Women were also doing more reproductive labour than men and were more likely to drop out of the labour force because of it. Analyses of capitalism in feminist political economy illustrate how capital accumulation depends on women's oppression in multiple, fundamental ways having to do with their paid and unpaid work. Women's work, and by extension their health, is the foundation upon which both production and social reproduction rely. Recognising the pandemic as endogenous to capitalism heightens the contradiction between a world shaped by the profit motive and the domestic and global requirements of public health.
Keywords: 2000 à aujourd'hui; 2020-2029; approches et analyses; capitalisme; covid-19; histoire et politique; patriarcat; projet charge mentale; périodes historiques; racisme; ressource en ligne; santé; sexisme; systèmes d'oppressions; thématiques; violences

La puissance féministe - Gago, Verónica (Éditions de la rue Dorion, 2021)
L’Amérique du Sud est un des coeurs battants du féminisme contemporain. Des millions de femmes y prennent la rue contre les féminicides, les violences qui frappent les minorités de race et de genre, les lois qui répriment l’avortement et le développement néo-extractiviste. Figure majeure du féminisme latino-américain, Verónica Gago réinscrit ces bouleversements dans l’émergence d’une internationale féministe et propose, avec La puissance féministe, un antidote à tous les discours de culpabilité et de victimisation. En se réappropriant l’arme classique de la grève, en construisant un féminisme populaire, radical et inclusif, les mouvements sud-américains ont initié une véritable révolution. C’est à partir de l’expérience de ces luttes que Gago reconceptualise la question du travail domestique et de la reproduction sociale, expose les limites du populisme de gauche et dialogue avec Spinoza, Marx, Luxemburg ou Federici. Parce qu’il unit la verve politique du manifeste aux ambitions conceptuelles de la théorie, La puissance féministe est un livre majeur pour saisir la portée internationale du féminisme aujourd’hui.
Keywords: 2000 à aujourd'hui; amérique latine; amériques; approches et analyses; care; cours; cycles supérieurs; fem7000; histoire et politique; justice sociale; militance; patriarcat; périodes historiques; régions géographiques; systèmes d'oppressions; thématiques; violences

Hidden in plain sight: Gender analysis of the environmental and social impact assessment of the East African crude oil pipeline - Hill, Christina; Namara, Charité; Orcaya, Jane; Bogrand, André; Sellwood, Scott A. (Impact Assessment and Project Appraisal, 2021)
Large-scale mining, oil, and gas projects can have a profound and negative affect on women’s rights and gender equality. Adverse impacts include the disruption of family and social life; the increased risks to health and safety, especially in terms of domestic and sexual violence; environmental degradation; as well as changing access to and control over land and livelihoods. These adverse impacts fall most heavily on women. This case study focused on the East African Crude Oil Pipeline (EACOP). It shows that conventional environmental and social impact assessment (ESIA) processes may not identify all potential adverse impacts on women, and can fail to analyse the implications of potential impacts on gender norms and gender power relations, leading to a downplaying of the significance of these impacts. The implications for women and girls’ health and safety resulting from the in-migration of large numbers of mostly men seeking project employment and other opportunities and increases in women’s unpaid care work are two potential adverse impacts the EACOP ESIA failed to identify. Strengthening gender analysis within the current suite of impact assessment tools and methodologies, particularly for extractive industries projects, is therefore urgently needed. © 2021 IAIA.
Keywords: 2000 à aujourd'hui; afrique; approches et analyses; environnement; extractivisme; industrie pétrolière; ouganda; patriarcat; projet charge mentale; périodes historiques; rapports sociaux de sexe; régions géographiques; santé; santé des femmes*; systèmes d'oppressions; thématiques; violences

Patriarcavirus, feminist dystopias and COVID-19: Reflections on the phenomenon of gender pandemics - Machado-Jiménez, Almudena (Feminismo/s, 2021)
This essay examines contemporary feminist dystopias to study the phenomenon of gender pandemics. Gender pandemic narrative allegorises possible aftermaths of patriarcavirus, unleashing many natural disasters that force global biopolitics to hinder gender equality. The main objective of this essay is to explain how gender pandemics are appropriated in patriarchal utopian discourses as a pretext to control female empowerment, diagnosing women as diseased organisms that risk the state’s well-being. Moreover, the novels explore the interdependence between biology and sociality, portraying the acute vulnerability of female bodies during and after the pandemic conflicts, inasmuch as patriarchal power arranges a hierarchical value system of living that reinforces gender discrimination. Particularly, the COVID-19 emergency is analysed as a gender pandemic: the exacerbated machismo and the growing distress in the female population prove that women are afflicted with a suffocating patriarcavirus, which has critically gagged them in the first year of the pandemic.
Keywords: 2000 à aujourd'hui; 2010-2019; 2020-2029; approches et analyses; arts; corps; covid-19; discipline; droits des femmes*; genre; patriarcat; précarité; périodes historiques; ressource en ligne; santé; systèmes d'oppressions; thématiques; violences; études littéraires

Après la charge mentale, la charge écologique ? Au vert avec la dessinatrice Emma - Vert (2021)
Grâce à ses bédés pédagogiques et engagées, elle a popularisé le concept de "charge mentale" avant de s'attaquer à un tas d'autres sujets compliqués, dont le climat. Avec la dessinatrice féministe Emma, nous avons discuté d'écologie au sein du foyer, de l'égalité femmes-hommes à l'épreuve de l'"effondrisme" et des petits gestes contre la fin du monde.
Keywords: 2000 à aujourd'hui; 2020-2029; anticapitalisme; approches et analyses; charge environnementale; charge mentale; charge émotionnelle; environnement; europe; france; patriarcat; projet charge mentale; périodes historiques; ressource en ligne; régions géographiques; systèmes d'oppressions; thématiques; travail; travail invisible; violences

Dead white men vs. Greta Thunberg: Nationalism, misogyny, and climate change denial in swedish far-right digital eedia - Vowles, Kjell; Hultman, Martin (Australian Feminist Studies, 2021)
In the autumn of 2018 Greta Thunberg started her school strike. Soon she and the Fridays For Future-movement rose to world-fame, stirring a backlash laying bare the intrinsic climate change denial of Swedish far-right digital media. These outlets had previously been almost silent on climate change, but in 2019, four of the ten most read articles on the site Samhällsnytt were about Thunberg, all of them discrediting the movement and spreading doubt about climate science. Using the conceptualisation of industrial/breadwinner masculinities as developed by Hultman and Pulé [2018. Ecological Masculinities: Theoretical Foundations and Practical Guidance. Routledge Studies in Gender and Environments. New York: Routledge], this article analyses what provoked this reaction. It explores how the hostility to Thunberg was constructed in far-right media discourse in the years 2018–2019, when she became a threat to an imagined industrial, homogenic and patriarchal community. Using conspiracy theories and historical tropes of irrational femininity, the far right was trying to protect the usually hidden environmental privileges, related to unequal carbon emissions and resource use, that Thunberg and her movement made visible. © 2022 The Author(s). Published by Informa UK Limited, trading as Taylor & Francis Group.
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; discous dominant; environnement; europe; extrême-droite; histoire et politique; misogynie; médias; patriarcat; projet charge mentale; périodes historiques; régions géographiques; sexisme; stéréotypes de genre; suède; systèmes d'oppressions; thématiques; violences